Improving Mechanisms for Increasing the Competitiveness of Services (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article describes the importance of competition, the main mechanism of the market economy, in the development of the service sector and the analysis of the factors affecting it.